Structural rearrangements during sub-Tg relaxation and nucleation in lithium disilicate glass revealed by a solid-state NMR and MD strategy. (November 2022) - Bradtmüller, Henrik; Gaddam, Anuraag; Eckert, Hellmut; Zanotto, Edgar D.
Abstract: Structural rearrangements taking place during relaxation and crystal nucleation in lithium-disilicate (LS2) glass have been investigated by a comprehensive set of solid-state nuclear magnetic resonance (NMR) experiments, supported by molecular dynamics (MD) simulations. Samples were subjected to heat treatments at 435 °C, i.e., 20 K below the laboratory glass transition temperature ( T g ). Raman and NMR data indicate that under these conditions both relaxation and nucleation occur without detectable changes in the network former unit distribution of the glassy silicon-oxide network. Instead, relaxation of the frozen supercooled melt and nucleation of LS2 crystals occur principally in terms of a changing lithium local environment: 7 Li spin-echo decay NMR indicates average Li-Li distances, characterized by homonuclear dipolar second-moment measurements, are reduced after very short heat treatments and approach those found in the isochemical crystal. This finding is supported by molecular dynamics (MD) simulations predicting a dependence of the Li + ion distribution on the melt-cooling rate. In addition, the structural reorganization also impacts the distribution of electric field gradients as detected by 7 Li satellite transition NMR spectroscopy. Finally, crystal nucleation becomes most evident by the appearance of minor amounts of sharp 29 Si MAS resonances and a significant change in the 7 Li NMR satellite transitions, as visualized by difference spectroscopy. This study defines a new NMR strategy, generally applicable for investigating the structural relaxation process accompanying the internal crystallization of ion-conducting frozen supercooled melts containing suitable NMR active nuclear probes ( 7 Li, 23 Na, 133 Cs, etc.). Graphical abstract: Image, graphical abstract